2020
DOI: 10.30773/pi.2020.0157
|View full text |Cite
|
Sign up to set email alerts
|

Shape and Volumetric Differences in the Corpus Callosum between Patients with Major Depressive Disorder and Healthy Controls

Abstract: Objective This study aimed to investigate the morphometric differences in the corpus callosum between patients with major depressive disorder (MDD) and healthy controls and analyze their relationship to gray matter changes.Methods Twenty female MDD patients and 21 healthy controls (HCs) were included in the study. To identify the difference in the regional gray matter concentration (GMC), VBM was performed with T1 magnetic resonance imaging. The shape analysis of the corpus callosum was processed. Diffusion te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Finally, some reviewed studies ( 29 , 35 , 38 ) found higher FA and lower AD in CC between responders and non-responders at the end of antidepressant medications. The CC has been consistently found disrupted in MDD patients, especially the genu, where a decrease of FA, probably connected with a reduction of axonal fibers ( 67 ), has been largely reported ( 68 , 69 ). According to WM neuroanatomy, the axonal fibers originating from genu constitute forceps minor, a well-known clinical biomarker for MDD treatment ( 38 ), and reach the frontal regions ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some reviewed studies ( 29 , 35 , 38 ) found higher FA and lower AD in CC between responders and non-responders at the end of antidepressant medications. The CC has been consistently found disrupted in MDD patients, especially the genu, where a decrease of FA, probably connected with a reduction of axonal fibers ( 67 ), has been largely reported ( 68 , 69 ). According to WM neuroanatomy, the axonal fibers originating from genu constitute forceps minor, a well-known clinical biomarker for MDD treatment ( 38 ), and reach the frontal regions ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, regional structural changes in the corpus callosum might contribute to the impaired cognition and emotional regulation. At present, more and more studies have reported the relationship between corpus callosum changes and affective disorders (Lee et al., 2020 ; Lin et al., 2020 ). Studies have found that corpus callosum damage or thinning has been shown to be associated with decreased function in executive function, attention, working memory, processing speed, verbal fluency, and memory tests in both healthy and patient groups (Redmond et al., 2018 ; Van Schependom et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with corpus callosotomy exhibited severe, nonreversible interhemispheric connectivity disruption in several brain regions [ 19 ]. In major depressive disorder (MDD), fibers crossing genu, rostrum, and splenium were also reported anatomically damaged, accompanied by damage to the grey matter in the corresponding areas [ 20 ]. The injury of the middle part of CC may serve as an imaging biomarker for generative anxiety disorder (GAD) patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%